Utilization Of Technology In Ethnomathematics-Based Geogebra Learning Media - Sianipar, Hikmatul Fadhilah; Nuranisah, Nuranisah; Silalahi, Trinidad (Jurnal Media Computer Science, 2025)
This study aims to analyze the effectiveness of utilizing GeoGebra technology as a mathematics learning medium integrated with ethnomathematics concepts in enhancing students' understanding of geometry material. The background of this research is based on low student interest and learning outcomes in mathematics subjects, particularly geometry, as well as the need to integrate local culture in learning to create more meaningful contexts. The research method used is Systematic Literature Review (SLR) to review existing literature on the use of technology in ethnomathematics-based learning. A total of 15 relevant articles from the last 5 years were selected and analyzed using SLR to determine technology opportunities in creating culturally-based learning media. The article selection process used strict inclusion and exclusion criteria, with searches through academic databases such as Google Scholar using keywords "ethnomathematics", "GeoGebra", "technology", and "mathematics education". The findings from the literature review indicate that digital technology, particularly GeoGebra, has great potential in developing mathematics learning media. The articles analyzed consistently report improvements in learning interest, conceptual understanding, and appreciation of local culture when technology is used as a bridge between formal mathematics and ethnomathematics.